Solvability of a System of Nonconvex General Variational Inequalities - Thakur, Balwant Singh; Varghese, Suja (Sarajevo Journal of Mathematics, 2024)
Using the prox-regularity notion, we introduce a system of nonconvex general variational inequalities and a general three step algorithm for approximate solvability of this system. We establish the convergence of three-step projection method for a general system of nonconvex variational inequality problem. We obtain as a particular case some known results. 2000 Mathematics Subject Classification. 47J20, 65K10, 65K15, 90C33